Explorações, experimentações e intervenções em São Paulo: estudo de caso sobre o Programa Jovens Urbanos - Aboboreira, Ariane (2014)
This investigation has as its main objective to analyse, in the specific situation of the Program "Urban Youth" - CENPEC and Itau Social Foundation - what are the impacts on their young participants within their experimentations in Sao Paulo metropolitan area. By evaluating the proposal of the program - which combines explorations in the city, experimentations of new technologies and interventions on the neighborhoods in which the participants are residents - this investigation intends to: understand how the movement of the young participants around the city - and the perception they acquire in the relation with new ways of appropriation and uses of the metropolis - resonates in the resignifications they make about their resident neighborhood; it is also the objective, to answer how these mobile perceptions interfere in the interventions promoted by the end of the "Urban Youth" program. The young participant's narrative is the basis of the methodological axis of this investigation but the research also has as fundamentals:the evaluation of official documents distributed by the "Urban Youth" program, blog analysis; and also with ethnografical practices centered on field research and based on participant observation and interviews